A Devil's dictionary for mental health. (October 2017) - Timms, Philip
Summary: Clinical psychiatry, for all its emphasis on scientific rigour, is mediated mainly by words rather than by numbers. As with other professional areas, it has developed its own set of jargon words and phrases. Many of these are not the technical terms traditionally seen as jargon, but standard English words and phrases used in an idiosyncratic way. They therefore go unnoticed as jargon, while enfeebling our communications. I have used the template of Ambrose Bierce's The Devil's Dictionary to highlight some examples, with the aim of helping us all to talk, write and, perhaps, think more clearly.